STUDI ETNOPEDAGOGI TENTANG PENDIDIKAN ANAK DALAM KELUARGA MASYARAKAT BATAK DI MEDAN DENAI BERBASIS NILAI-NILAI KEARIFAN LOKAL - Sarah Nasution (UNIVERSITAS DHARMAWANGSA, 2025)
The rapid development of artificial intelligence (AI) has significantly transformed educational practices, including the way students engage in academic writing. AI-assisted tools such as ChatGPT, Grammarly, QuillBot, Gemini, and other AI-powered applications are increasingly being used by students to support various stages of the writing process. These technologies provide assistance in generating ideas, correcting grammar, improving vocabulary, organizing content, and revising written texts. As digital technologies become more integrated into students’ daily lives, understanding how learners experience the use of AI-assisted tools in academic writing has become an important area of educational research. Therefore, this study aims to explore the experiences of SMA Dharmawangsa students in using AI-assisted tools for academic writing, identify the perceived benefits and challenges, and examine students’ perspectives on the role of AI in supporting their writing development.This study employed a qualitative approach using a phenomenological research design. The participants were students of SMA Dharmawangsa who had experience using AI-assisted tools in completing academic writing tasks. Participants were selected through purposive sampling based on specific criteria relevant to the research objectives. Data were collected through semi-structured interviews, observations, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which involved data reduction, data display, and conclusion drawing. To ensure the trustworthiness of the findings, triangulation, member checking, and peer debriefing were applied.The findings revealed that students generally had positive experiences using AI-assisted tools in academic writing. Students perceived AI technologies as useful learning resources that helped them generate ideas, improve grammar and vocabulary, organize essays, and revise their writing more effectively. The use of AI-assisted tools also increased students’ confidence and supported independent learning by providing immediate feedback during the writing process. Furthermore, students reported that AI technologies helped them complete writing tasks more efficiently and reduced difficulties commonly encountered in academic writing. However, several challenges were identified, including the tendency to rely excessively on AI-generated content, concerns regarding the accuracy of information provided by AI systems, and uncertainty about the ethical boundaries of AI use in academic work. Despite these challenges, most participants recognized the importance of using AI responsibly and maintaining originality in their writing.The study concludes that AI-assisted tools have significant potential to support students’ academic writing development when used appropriately. AI technologies can enhance writing quality, foster learner autonomy, and increase engagement in writing activities. Nevertheless, effective use of AI requires students to critically evaluate AI-generated suggestions and maintain academic integrity. The study proposes the concept of Responsible AI-Assisted Academic Writing, which emphasizes the role of AI as a learning companion rather than a replacement for students’ critical thinking and writing abilities. The findings contribute to the growing body of research on artificial intelligence in education and provide practical insights for teachers, schools, and policymakers in promoting ethical and effective AI integration in academic writing instruction.